2019
DOI: 10.1002/jccs.201900076
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of role of urea in morphologically controlled synthesis of calcium‐bismuth bimetallic nanoparticles from chicken egg shells and its catalytic and fuel additive applications

Abstract: A comparative study on the role of urea in controlling the morphology of calcium‐bismuth (Ca5Bi3) bimetallic nanoparticles is carried out. Calcium‐bismuth bimetallic nanoparticles are synthesized in the presence and absence of urea using the solvothermal method. The morphology of the synthesized products is analyzed by scanning electron microscopy. The composition of the product is analyzed by energy‐dispersive X‐ray spectroscopic and X‐ray diffraction (XRD) analyses. Reitveld refinements are performed on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…The micrographs, obtained from SEM study, showed (Fig. 1a and 1b) that the surfaces of UES contained pores with well-developed cavities and exhibited crystallinity and irregular angular pattern of fractures (Khan et al, 2019).…”
Section: Sem Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The micrographs, obtained from SEM study, showed (Fig. 1a and 1b) that the surfaces of UES contained pores with well-developed cavities and exhibited crystallinity and irregular angular pattern of fractures (Khan et al, 2019).…”
Section: Sem Studymentioning
confidence: 99%
“…The diffractogram (Fig. 2) indicated that UES possessed calcite structures with a similarity to calcium carbonate mineral (2 = 29.305 nm) (Khan et al 2019) and particle size was found in the range 40-50 nm (D = 44.822 nm) from the Scherrer formula.…”
Section: Xrd Studymentioning
confidence: 99%
“…Among these additives, surfactants are the most used ones. They lower the surface tension at the interface between nanoparticles and prevent particle agglomeration by lowering the surface energy of the nanoparticle, which, in turn, also defines the particle size and morphology. Alongside surfactants, urea is one of the highly sought-after agents in nanomaterial synthesis over a conductive fabric substrate, owing to its high water solubility, low hydrolysis temperature, controllable hydrolysis rate, and ability to form hydrogen bonds with solvents. …”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] Particularly, organic compounds such as phenol and halogenated phenols are very hazardous and even carcinogenic. [ 6,7 ] In order to safeguard human health, it is urgently required to remove these substances from the atmosphere before they further extend their unbearable problems.…”
Section: Introductionmentioning
confidence: 99%